Model of Integrated/Sustainable Solid Waste Management in Republic of Srpska – comparative analysis between two different municipalities - Milan Topić; Ljubiša Preradović (AGG+, 2014)
Establishing an Integrated/Sustainable Solid Waste Management (ISWM) system that is accessible and financially supported represents a significant challenge for Republic of Srpska. Fragmentation of solid waste collection and disposal systems, technically unapproved landfills, absence of treatment technologies and insufficient number of recycling centers are some of identified problems. In order to identify the effectiveness in delivering SWM services and to emphasize the problems, the ISWM model was developed and tested on the case studies. This model illustrates a current practice in WM for two selected municipalities (Banja Luka and Šipovo).